2004
DOI: 10.1021/bm049501t
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Controlled Association of Protein with a Dynamic Nanogel of Hydrophobized Polysaccharide and Cyclodextrin:  Heat Shock Protein-Like Activity of Artificial Molecular Chaperone

Abstract: Dynamic CHP-CD nanogels, which consisted of a self-assembly of cholesteryl-group-bearing pullulan (CHP) and beta-cyclodextrin (CD), were characterized by SEC and SEC-MALS methods. The nanogels prevented the thermal aggregation of carbonic anhydrase B (CAB) by selective trapping of the heat-denatured protein. After the complex between the CHP-CD nanogels and CAB was cooled, the enzyme activity of CAB spontaneously recovered upon release from the complex. The dynamic nanogels self-regulated an association of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 33 publications
1
79
0
Order By: Relevance
“…[15][16][17][18] The hydrogel NPs can also be used as a drug carrier system in medicine 17,19,20 as well as artificial molecular chaperones in biotechnology. [21][22][23] On the basis of these, our group developed a new method to synthesize cholesterol-modified pullulan (CHSP) by directly grafting proper cholesterol residues onto pullulan using succinyl linkages, thus providing a new strategy for the effective and safe synthesis of CHSP. In vitro studies indicated that CHSP self-assembled NPs showed potential as a sustained-release carrier of mitoxantrone.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The hydrogel NPs can also be used as a drug carrier system in medicine 17,19,20 as well as artificial molecular chaperones in biotechnology. [21][22][23] On the basis of these, our group developed a new method to synthesize cholesterol-modified pullulan (CHSP) by directly grafting proper cholesterol residues onto pullulan using succinyl linkages, thus providing a new strategy for the effective and safe synthesis of CHSP. In vitro studies indicated that CHSP self-assembled NPs showed potential as a sustained-release carrier of mitoxantrone.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results indicate that CHP nanogels can selectively trap unfolded proteins or refolding intermediates [21][22][23] that expose relatively hydrophobic domains to the aqueous solution. Thus, one hypothesis to explain the inhibition of GFP folding is that the unfolded or partially folded GFP peptides become trapped in the hydrogel matrix of CHP nanogels.…”
Section: Nanogel Chaperone In Cell-free Protein Synthesis Y Sasaki Et Almentioning
confidence: 99%
“…20 For example, nanogels formed with cholesteryl group-bearing pullulan (CHP) can trap heatdenatured proteins 21 or chemically denatured proteins (that is, protein-refolding intermediates formed after chemical denaturation by urea or guanidinium hydrochloride). 22,23 The CHP nanogel consists of stable monodisperse nanoparticles (B30 nm) with B4-5 CHP polymers per nanogel and approximately eight non-covalent crosslinking regions that consist of cholesteryl groups. [24][25][26] The structure of the CHP nanogel is disrupted by the addition of cyclodextrins and the protein complexed with the nanogel is released and folds into its mature form, so that the CHP nanogels and cyclodextrins together function as an artificial chaperone.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, carbonic anhydrase (CA), lipase and aamylase were selected as target proteins, which are easy to assay their activity; they are often used as a model enzyme to examine the stability and improvement of the activity. 15,31,32 EXPERIMENTAL PROCEDURE Materials gPGAs (sodium salt form, molecular weight: 50 and 500 kDa) were commercial products of BioLeaders Corp. (Daejeon, Korea). CA from bovine erythrocytes, Amano lipase AK from Pseudomonas fluorescens, a-amylase type VI-B from porcine pancreas, p-nitrophenyl acetate (pNPA), fluorescein isothiocyanate (FITC) isomer I and phosphate-buffered saline (pH 7.4) were purchased from Sigma-Aldrich (St Louis, MO, USA).…”
Section: Introductionmentioning
confidence: 99%